Synthesis and Characterization Composite Fe3O4/Chitosan-PVA/TiO2 for Photocatalytic Degradation of Tetracycline - Denada, Laellia; Poedji Loekitowati Hariani; Addy Rachmat (The Journal of Pure and Applied Chemistry Research, 2025)
This research aims to synthesize tetracycline waste which pollutes the environment, can be overcome by a photocatalytic degradation process using a Fe3O4/Chitosan-PVA/TiO2 composite synthesized using the coprecipitation method. The Fe3O4/Chitosan-PVA/TiO2 composite was characterized by X-Ray Diffraction (XRD), Scanning Electron Microscope- Energy Dispersive Spectroscopy (SEM-EDS), Vibrating Sample Magnetometer (VSM), Ultraviolet-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS) and pHpzc. The crystallite size of 28.29 nm. The morphology of the composite shows a heterogeneous form with the constituent elements being C (7.69%), N (12.78), O (14.88%), Fe (63.33%) and Ti (1.29%). The saturation magnetization value of 64.24 emu/g is superparamagnetic with a band gap value of 1.38 eV and pHpzc at pH 6.8. The degradation process was studied by investigating the influence of several parameters, namely, solution pH, tetracycline concentration and irradiation time. The efficiency of tetracycline degradation by Fe3O4/Chitosan-PVA/TiO2 was 94.85% at pH 2, concentration of 15 mg/L and radiation time of 70 minutes. The results of Total Organic Carbon (TOC) analysis in a 15 mg/L tetracycline solution before degradation were 20.3 mg/L and after degradation were 5.59 mg/L with a percent reduction in carbon content of 72.46%.